Guaranteed Minimum Income Schemes in Europe : Landscape and Design - Coady, David; Jahan, Samir; Matsumoto, Riki.; Shang, Baoping (Washington, D.C. : International Monetary Fund, 2021)
This paper provides an overview of the design of means-tested Guaranteed Minimum Income schemes, which constitute an important component of social protection systems in European countries. It discusses how key design features differ across countries, including how countries balance the primary objective of poverty alleviation against the desire to both manage the work disincentives inherent in such programs and contain fiscal cost. The analysis finds a clear trade-off between both concerns in practice, with many countries combining low generosity with low benefit withdrawal rates (BWRs) thus prioritizing employment incentives over the primary objective of poverty alleviation. Many countries can reduce this trade off by combining higher generosity with higher BWRs. Countries with very high BWRs should consider reducing these, including through allowing income disregards and time dependent (rather than income-dependent) benefit withdrawal. The work disincentives associated with higher BWRs can also be attenuated through strengthening complementary activation policies that incentivize and support participation in the labor market.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Efficiency; Government Policy; National Government Expenditures and Welfare Programs; Optimal Taxation; Provision and Effects of Welfare Program